2019
DOI: 10.3390/ma12233951
|View full text |Cite
|
Sign up to set email alerts
|

Chain Model for Carbon Nanotube Bundle under Plane Strain Conditions

Abstract: Carbon nanotubes (CNTs) have record high tensile strength and Young’s modulus, which makes them ideal for making super strong yarns, ropes, fillers for composites, solid lubricants, etc. The mechanical properties of CNT bundles have been addressed in a number of experimental and theoretical studies. The development of efficient computational methods for solving this problem is an important step in the design of new CNT-based materials. In the present study, an atomistic chain model is proposed to analyze the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0
3

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 69 publications
1
31
0
3
Order By: Relevance
“…7(b) and (c), top row. Both these structures have been described in [61]. In this regime all CNTs have elliptic, non-collapsed cross section for all three loading schemes.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…7(b) and (c), top row. Both these structures have been described in [61]. In this regime all CNTs have elliptic, non-collapsed cross section for all three loading schemes.…”
Section: Discussionmentioning
confidence: 99%
“…The Hamiltonian of the chain model employed in this study together with the model parameters can be found in [61]. It includes four terms,…”
Section: Simulation Detailsmentioning
confidence: 99%
See 2 more Smart Citations
“…Here the mechanical properties of CNT bundle under lateral compression will be addressed in frames of the chain model offered in [69] and modified for the CNT bundle in [70]. The efficiency of the chain model in modelling secondary sp 2 -carbon structures such as folded and scrolled carbon nanoribbons has been demonstrated in a series of works [69][70][71][72][73][74][75].…”
Section: Introductionmentioning
confidence: 99%